Evaluation of Spironolactone in Combination with Furosemide in Cirrhotic Patients with Permagna (Large) Ascites - Tuty Mulyani; Fita Rahmawati; Neneng Ratnasari (Faculty of Pharmacy, Universitas Gadjah Mada)
Ascites happens in 50% of patients with liver cirrhosis, Some of them experienced permagna ascites (large ascites). Based on the European Association for the Study of the Liver (EASL) guidelines in 2010, therapy of permagna ascites (large ascites) is paracentesis followed by restriction of sodium intake and diuretics. The use of diuretics can cause side effects such as hyperkalemia and hypokalemia. The aims of this study is to determine the effectiveness and safety of the combination of spironolactone and furosemide in patients with liver cirrhosis with permagna ascites.This study was an analytical observational study with retrospective cohort design. This study was done through a search of cirrhotic patients with permagna ascites’ medical record during January 2010-December 2014. This study was conducted at RSUP Dr. Sardjito. A total of 19 subjects categorized in the tense group and 39 subjects were in non-tense group. The effectiveness of diuretics seen by decreasing 1 cm/day of the patient's abdominal girth daily and the achievement of minimum of fluid balance -500 ml/day. Effectiveness data was analyzed by using independent t-test statistic. Side effects data was analyzed descriptively. There are no significantly different in reduction of abdominal girth and achieving fluid balance between cirrhotic patients with tense and non-tense ascites (p> 0.05); Adverse events of diuretics occurs in 5 patients, consist of hypokalemia 2 patients (3.45%), hyperkalemia 2 patients (3.45%) and hyponatraemia 1 patient (1.72%).